Semisynthesis, biological activities, and mechanism studies of Mannich base analogues of magnolol/honokiol as potential α-glucosidase inhibitors. (1st December 2022) - Chu, Junyan; Yang, Ruige; Cheng, Wanqing; Cui, Liping; Pan, Hanchen; Liu, Jifeng; Guo, Yong
Graphical abstract: Highlights: Thirty new Mannich base analogues of magnolol/honokiol were prepared. Compounds 3k and 3l showed better α -glucosidase inhibitory activity than acarbose. Compounds 3k and 3l are noncompetitive inhibitors with low toxicity to normal cells. Molecular docking further validated that 3k and 3l are noncompetitive inhibitors. Abstract: Magnolol and honokiol, derived from a Magnolia officinalis Rehd. et Wils, are a class of natural biphenolic lignans. Currently, the discovery of new α -glucosidase inhibitors from natural analogues is of interest. Here, four series of thirty new Mannich base analogues of magnolol/honokiol were prepared and evaluated for their α -glucosidase inhibitory activities. Among these Mannich base analogues of magnolol/honokiol, 3k and 3l exhibited more potent inhibitory effects on α -glucosidase than the reference drug acarbose, and their IC50 values were 14.94 ± 0.17 µM and 13.78 ± 1.42 µM, respectively. Some interesting structure–activity relationships (SARs) were also analyzed. The enzyme inhibition kinetics indicated that 3k and 3l were noncompetitive inhibitors. This result was in agreement with molecular docking studies, where the binding sites of 3k and 3l to α -glucosidase were different from that of the competitive inhibitor acarbose to α -glucosidase. Moverover, compounds 3k and 3l exhibited low toxicity to normal cells (LO2). Thus, analogues 3k and 3l could be deeply developed for the discovery of natural products based antidiabetic candidates.